2020
DOI: 10.3390/cancers12071818
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Antitumoral Effects of Cytokine-Induced Killer Cells by Antibody-Mediated Inhibition of MICA Shedding

Abstract: Natural killer group 2D (NKG2D) receptor plays a pivotal role in cytokine-induced killer (CIK) cell-mediated cytotoxicity against malignancies, and the expression of NKG2D ligands might allow targets to be more susceptible to the CIK cell-mediated destruction. In this study, we investigated the synergistic effects of CIK cells antitumor activity and antibody-mediated inhibition of MICA/B shedding. This monoclonal antibody (7C6) has been previously shown to be able to specifically target MICA/B a3 domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…CD137 is a costimulating molecule that acts on the activation of T cells, regulating the activity of these cells in physiological and pathological processes [ 108 ]. Wang was one of the authors of a study that tested two types of mAbs for the treatment of hemophilia [ 109 ], and Zhang participated in a study whose objective was to evaluate the performance of monoclonal antibody 7C6 in marking MICA/B a3, a domain present in tumor cells, potentiating the activity of antitumor CIK cells [ 110 ]. Other studies of the main authors cited and other researchers are given in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…CD137 is a costimulating molecule that acts on the activation of T cells, regulating the activity of these cells in physiological and pathological processes [ 108 ]. Wang was one of the authors of a study that tested two types of mAbs for the treatment of hemophilia [ 109 ], and Zhang participated in a study whose objective was to evaluate the performance of monoclonal antibody 7C6 in marking MICA/B a3, a domain present in tumor cells, potentiating the activity of antitumor CIK cells [ 110 ]. Other studies of the main authors cited and other researchers are given in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the strategy for preventing surface loss or upregulating the expression of NKG2D ligands may help to enhance the cytolytic ability of CIK cells against these tumors. We have previously shown that the cytotoxicity of CIK cells was enhanced by stabilization of MICA/B on tumor cells through selective small-molecule inhibitors or a specific anti-MICA monoclonal antibody (51,52). Furthermore, the ligands of NKG2D can be induced or upregulated by chemotherapeutic agents or radiation therapy (53,54); thus, the combination therapy of CIK cells with these traditional modalities might have synergistic benefits for cancer patients and further studies are needed in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Approval of the ethics committee of the University Hospital Bonn was obtained, including signed informed consent from the volunteers. CIK cells were generated as previously described protocol ( 14 ). Briefly, a standard gradient density centrifugation using Pancoll (Pan-Biotech) was performed.…”
Section: Methodsmentioning
confidence: 99%